2022
DOI: 10.1055/s-0042-1747676
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Association of Tumor Budding, Tumor Microenvironment, and Clinicopathological Characteristics of Invasive Breast Carcinoma

Abstract: Background Tumor budding (TB) has been identified in many solid cancers and thought to be involved in invasion and is the initial step in the metastatic process. Limited information is available documenting the role of tumor budding in breast carcinoma. With this aim, the present study evaluates the association of tumor budding, tumor microenvironment, and its correlation with clinicopathologic parameters. Materials and Methods A total of 102 cases were archived and evaluated for peripheral and intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Therefore, many previous studies have found similar associations between TB and LVI, pT, and axillary lymph node metastasis 4 , 6 , 8 , 15 , 17 20 . In line with them, we found a significant association.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Therefore, many previous studies have found similar associations between TB and LVI, pT, and axillary lymph node metastasis 4 , 6 , 8 , 15 , 17 20 . In line with them, we found a significant association.…”
Section: Discussionmentioning
confidence: 66%
“…In the ensuing years, it has been studied in many solid organ malignancies as a prognostic marker 4 , 13 , 14 . Therefore TB is advocated as a more sensitive prognostic factor, a predictor of aggressiveness and a worse outcome 4 , 6 , 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Group I (grade I), tumor with 0 to 4 tumor buds, Group II (grade II), tumor with 5 to 10 tumor buds; and Group III (grade III), tumor with more than 10 tumor buds. 17 …”
Section: Methodsmentioning
confidence: 99%
“…Tumor budding is associated with various clinicopathological characteristics like age, laterality, tumor size, tumor grade, histological subtypes, inflammation, lymph node and, lymphatic/vascular invasion, ER, PR, Her2Neu, treatment status, pTN-Mstaging [3][4][5] . Tumor buds are helpful in predicting the response to neoadjuvant chemotherapy in breast carcinoma patients [5] .…”
Section: Introductionmentioning
confidence: 99%